Pengaruh Debt to Equity Ratio, Current Ratio dan Inventory Turnover terhadap Return On Asset pada subsektor food & beverage di Bursa Efek Indonesia Periode 2021-2024 - Dinadia, Dinadia; Budianto, Erwin (Jurnal GeoEkonomi, 2026)
The purpose of this study is to determine the impact of Debt to Equity Ratio (DER), Current Ratio (CR), and Inventory Turnover (ITO) on Profitability in the Food and Beverage sub-sector listed on the Indonesia Stock Exchange (IDX) in 2021-2024. Sampling in this study used purposive sampling, while the data analysis applied was multiple linear regression analysis. The results of this study indicate that the Debt to Equity Ratio (DER) has a significant effect on Profitability, the Current Ratio (CR) also has a significant effect on Profitability, while Inventory Turnover (ITO) does not show a significant effect on Profitability.